BASIC CONCEPTS RELATED TO INTERNET CAPABILITIES AND INTERNET USAGE - Abdurazzakov Ilkhom Rustamovich (Web of Journals Publishing, 2024)
In this article, we discussed the possibilities of the Internet and the dangers of the Internet, the benefits of the Internet and the impact of the Internet on the minds of young people.
Keywords: International Network, structure of Internet network, social media, network.